Does capital account liberalisation make Caribbean economies more or less susceptible to sudden stops? - Jordan, Alwyn...[et al.] ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Explores the effect of liberalization on the 'sudden stop' of capital inflows.